Effect of Wind Turbine Blade Profile Surface Roughness on Ice Accretion – A Numerical Case Study. Issue 1 (November 2020) - Jin, Jia Yi; Virk, Muhammad S.
Abstract: A parametric numerical study of wind turbine blade profile surface roughness has been carried out to investigate its effects on boundary layer characteristics and accreted ice growth. DU96-W-180 blade profile is used in this paper. Multiphase numerical analysis has been performed at glaze ice conditions for three different surface roughness values: Shin et al. surface roughness model and two specific roughness values (0.03m and 0.0003m). Study shows that surface roughness considerably effects the shear stresses as well as heat fluxes, which results a variation of ice accretion in rate and shape. Results show that accreted ice mass and ice thickness increases with the increase of surface roughness.